Manajemen Investasi Publik dalam Mendukung Pembiayaan Pembangunan di Indonesia - Petra Ginting; Novie Indrawati Sagita (Relasi : Jurnal Ekonomi, 2025)
The target of Indonesia Emas 2045 in accordance with the direction of RPJPN 2025 - 2045 which is in line with the sustainable development of the country causes the state budget (APBN) to continue to increase over time. The role of public participation in financing state development can be an option for the government to go through public investment instruments issued by the government. Based on this, researchers are interested in conducting research entitled “Public Investment Management in Supporting Development Financing in Indonesia”. The research method used is descriptive qualitative method using a combination of literature study and field study. Researchers in conducting research collaborate two variables from the study results from the International Monetary Fund, namely Public Investment Management Assesment (PIMA) and George R Terry and Talidzuhu Ndraha through his book Kybernology (New Government Science), namely Government Management. Based on the results of this research, it can be concluded that in the implementation of public investment management, the government implements the four elements of public investment management from the IMF study. The government ensures that the issuance of public investment instruments, including Government Securities (SBN), is in accordance with the urgency of national development needs. The government also allocates the utilization of public investment to the right sectors and projects. Supervision is carried out by the government with the help of both government agencies / independent institutions at the central and regional levels.